Properties of ex-situ MgB2 bulk samples prepared by uniaxial hot pressing and spark plasma sintering - Haessler, W.; Scheiter, J.; Haedrich, P.; Kauffmann-Weiss, Sandra; Holzapfel, Bernhard; Oomen, M.; Nielsch, Kornelius (Physica C-Superconductivity and Its Applications, 2018)
The effect of compaction of ex-situ MgB2-powder, i.e. cold and hot uniaxial pressing, Spark Plasma Sintering (SPS) and of a post annealing on microstructure and superconducting properties of ex-situ bulk samples is studied. Additionally the impact of powder milling and the thermal stability of MgB2 are discussed. The magnetic critical current density can be enhanced by using of high energy milled powder and annealing at temperatures larger than 850 °C. The best properties were achieved by SPS processing of milled powder.
CRIS-Team Scopus Importer:2022-04-14